Knowledge of the Social Determinants of Health Among Nursing Students in a Public Nursing School in Tunisia - Mouhamed Kammoun; Fatma Zaouali; Yasmine Sakly; Salim Moussi; Hela Ghali (Public Health Nursing, 2026)
ABSTRACT Objectives To evaluate the knowledge of nursing students about Social Determinants of Health (SDH) at a public nursing school in Tunisia and identify associations with education, prior knowledge, socioeconomic status, and civic participation. Design A Quantitative analytical cross‐sectional study was conducted from January to March 2024. Sample Out of 386 eligible nursing students, 241 participated (response rate: 62.4%), primarily female (sex ratio: 0.65) with a mean age of 20.28 years. Measurements A structured electronic survey assessed participants' demographics, socioeconomic status, civic engagement, and knowledge of SDH through multiple‐choice questions and a scoring system (0–20 points). Intervention None. Results The mean SDH knowledge score was 13.44/20, with gaps observed in understanding key structural factors such as political policies, profit motive, and housing conditions. Media and personal experiences correlated with higher scores ( P = 0.001), while perceived curriculum inclusion and socioeconomic status had no significant effect. Most students found SDH content non‐engaging or irrelevant to practice. Conclusions Knowledge deficits among nursing students highlight a need for curriculum reform. Strategies such as active learning, simulations, and integration of SDH into clinical rotations are recommended. Increased political engagement and advocacy training are essential for addressing systemic health inequities effectively.